Nomogram predicting the likelihood of complications after surgery for deep endometriosis without bowel involvement - Clothilde Poupon; Clémentine Owen; Alexandra Arfi; Jonathan Cohen; Sofiane Bendifallah; Emile Daraï (Elsevier, 2019)
Study Objective: To describe complications following surgery for deep endometriosis (DE) without bowel involvement and to develop a nomogram for predicting postoperative complications. Design: Retrospective study Setting: Tertiary referral university hospital and expert center in endometriosis Patients: Two-hundred and twenty patients with DE without bowel involvement Interventions: Laparoscopic resection for DE without bowel involvement Measurements and Main Results: Operative complications were evaluated using the Clavien-Dindo classification. Voiding dysfunction was defined as a need for bladder self-catheterization lasting >1 month. Fifty-three patients (24%) had postoperative complications: 31 (14%) had a Clavien-Dindo grade III complication (3 grade I and 28 grade II); 11 (5%) had a grade III complication (2 grade IIIa and 9 grade IIIb); and 11 (5%) had voiding dysfunction. No grade IVV complications were observed. Age, Enzian classification risk group, and previous surgery for endometriosis were significantly associated with postoperative complications. The predictive model had an AUC of 0.72 (95% CI, 0.70-0.74) before and 0.70 (95% CI, 0.68-72) after bootstrap sample correction. The average difference and maximal difference in predicted and calibrated probabilities of recurrence were 0.023 and 0.089% respectively Conclusion: Surgery for DE without bowel resection is associated with a relatively high incidence of voiding dysfunction and postoperative complications mainly corresponding to Clavien-Dindo grade III. Age, risk group of Enzian classification, and previous surgery for endometriosis are significantly associated with postoperative complications and voiding dysfunction. Our results allowed us to build a nomogram which can be used to better inform patients about the risk of DE surgery without bowel involvement Keywords: ASRM classification, Clavien, Dindo classification, Deep endometriosis, Enzian classification, Postoperative complication